Tocilizumab for Severe and Critical COVID-19 Pneumonia in Queens, NYC. Issue 4 (July 2021) - Salama, Carlos; Kaplan-Lewis, Emma; Durrance, Richard; Wong, Linda; Arumugam, Vasanthi; Fabbri, Marilyn
Abstract : Background: New York City was hard hit by COVID-19. Elmhurst Hospital is a public hospital in Queens where more than 1500 patients were hospitalized with COVID. During the pandemic, various treatments were used with hopes of reducing the need for mechanical ventilation and death. Methods: We retrospectively reviewed charts of patients admitted from March 25 to April 3 with severe or critical COVID-19 pneumonia who received tocilizumab compared with a similar cohort who did not. Analyses were performed to determine differences in outcomes. Results: There was no observed difference in need for mechanical ventilation, length of stay, or mortality rate. In the tocilizumab-treated group, mechanical ventilation rate was 55%, and 49% of patients died. In the control group, 54% required mechanical ventilation and 46% died. Tocilizumab was overall well tolerated, although alanine aminotransferase elevation was more common in the tocilizumab-treated group. Conclusions: Tocilizumab failed to show short-term benefits in clinical outcomes in patients with hypoxic COVID pneumonia at our institution. Abstract : Supplemental digital content is available in the text.